PERBANDINGAN KUALITAS INPUT DAN PROSES PELAYANAN ANTENATAL YANG BERKUALITAS OLEH BIDAN DI PUSKESMAS KOTA SEMARANG BERDASARKAN STATUS AKREDITASI - Inna Maulina; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Accreditation is one of the media to improve the quality service in Primary Health Centre (PHC). One of the services in there is antenatal care. The quality of antenatal care from output K4 aspect is not accordance with the target. The purpose of this study is to analyze the comparison of input and process qualities of antenatal care in PHC both accredited and not. The type of this research is descriptive qualitative with comparative analysis. Data collection was done by in depth interview based on purposive sampling criteria of accreditation status and K4 coverage. The research subjects are 4 midwives who are responsible for antenatal as the main informants and triangulation informant are 1 Section Head of KIA Health Departement in Semarang, 4 Head of PHC, and 4 Laboratory Officers. The variables studied are personels, fund, SOP, infrastructure, planning, organizing, implementation and controlling. The results showed that the difference beetween accredited and not are in infrastructure, availability of SOP, and availability of controlling on midwifes’s compliance to SOP of antenatal. In other indicators, the situation in accredited almost the same as non. All midwives have not received special training on antenatal, planning was made when there was any visit and planning for antenatal coverage was done in mini workshop, both of them organizing cross sector, but the role of BPM in PHC with low K4 coverage still less in reporting. The implementation are still not up to the standard on counseling. The results of this study suggest that PHC need to makes SOP, increase cross-sector cooperation, and equip supporting facilities. Health Departement of Semarang needs to facilited special training of antenatal.